Chapter Ouverture: Santa Maria Novella e Firenze: convento e città - Panella, Emilio (Reti Medievali E-Book, 2020)
This Ouverture introduces the theme of the volume and highlights the convergences and inter- actions between the Commune of Florence and the Dominican convent of Santa Maria Novella by referring to a number of Remigio de' Girolami's sermons.